2007
DOI: 10.1534/genetics.106.063800
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Introgression and Recombination on Haplotype Structure and Linkage Disequilibrium Surrounding a Locus EncodingBymovirusResistance in Barley

Abstract: We present a detailed analysis of linkage disequilibrium (LD) in the physical and genetic context of the barley gene Hv-eIF4E, which confers resistance to the barley yellow mosaic virus (BYMV) complex. Eightythree SNPs distributed over 132 kb of Hv-eIF4E and six additional fragments genetically mapped to its flanking region were used to derive haplotypes from 131 accessions. Three haplogroups were recognized, discriminating between the alleles rym4 and rym5, which each encode for a spectrum of resistance to BY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 69 publications
(76 reference statements)
3
32
1
Order By: Relevance
“…Population structure, the target genomic region, and the number of polymorphic sites can all have a major impact on the pattern of LD and consequently, on the outcome of association studies (Akey et al 2003;Ke et al 2004;Pritchard et al 2000b). The population structure of the barley collection is largely consistent with the phenotype-based grouping into two-and six-rowed ear types, as has been noted in other sets of spring (Brantestam et al 2007;Hayes and Szucs 2006) and winter cultivars (Matus and Hayes 2002;Stracke et al 2007;Thiel et al 2003). Ear type is encoded by a single major gene v, located on chromosome 2H (Komatsuda et al 2007), which cannot account for the existence of genetically distinct subpopulations.…”
Section: Discussionsupporting
confidence: 69%
“…Population structure, the target genomic region, and the number of polymorphic sites can all have a major impact on the pattern of LD and consequently, on the outcome of association studies (Akey et al 2003;Ke et al 2004;Pritchard et al 2000b). The population structure of the barley collection is largely consistent with the phenotype-based grouping into two-and six-rowed ear types, as has been noted in other sets of spring (Brantestam et al 2007;Hayes and Szucs 2006) and winter cultivars (Matus and Hayes 2002;Stracke et al 2007;Thiel et al 2003). Ear type is encoded by a single major gene v, located on chromosome 2H (Komatsuda et al 2007), which cannot account for the existence of genetically distinct subpopulations.…”
Section: Discussionsupporting
confidence: 69%
“…The EIF4E protein is of crucial importance in organisms, as it is a component of the conserved eukaryotic translation initiation complex that interacts with the cap-structure of the host mRNAs and enables initiation of the translation of cellular proteins (Browning 1996; Kawaguchi and Bailey-Serres 2002). In previous EcoTILLING (a method for the discovery of natural nucleotide diversity) studies, no haplotypes carrying loss-of-function mutations in EIF4E were found in broad collections of accessions of a number of different crops and related wild plant species (Charron et al 2008; Hofinger et al2009, 2011; Ibiza et al 2010; Konecna et al 2014; Nieto et al 2007; Rubio et al 2009; Stein et al 2005; Stracke et al 2007). In the coding sequence of HvEIF4E , only non-synonymous mutations were previously identified in an Ethyl Methane Sulfonate (EMS) induced barley population (Gottwald et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Its value in barley has been demonstrated for various candidate genes and phenotypic traits (Haseneyer et al 2010;Matthies et al 2009a, b;Stracke et al 2007Stracke et al , 2009Malysheva-Otto et al 2006;Kraakman et al 2004Kraakman et al , 2006. Here, we report the sequence diversity present in barley SSI and SPSII, and use this variation to determine their influence over grain and malting quality.…”
Section: Introductionmentioning
confidence: 81%
“…As all SNP markers are found to be in complete linkage disequilibrium (LD) in the SSI gene, the resulting three main haplotypes were considered here for the association analysis (Table 1). High LD in barley is an important prerequisite for association mapping in candidate genes (Caldwell et al 2006;Rostoks et al 2006;Stracke et al 2007). A high LD was found between all eleven SNPs of SSI in the total set of 190 varieties and in the subpopulation of 96 winter barleys.…”
Section: Phenotype/genotype Association For Ssimentioning
confidence: 99%